Regional Development Banks: Theory And Practice - Alekseevna Bunich, Galina; Aleksandrovich Rovenskiy, Yuriy; Tambievna Akhvlediani, Julia; Yurievich Rusanov, Yury (Opción, 2019)
The international regional development banks are an international financial insti- tution, which was formed after the collapse of the colonial system to support the economic and social development of the countries liberated from colonial depend- ence, or the so-called developing countries. International development banks are a necessary center for the accumulation of financial resources, ensuring the solution of global socio-economic problems of the strategic development of the regional economy. At the current stage, the role and principles of international development banks are being transformed. From the international institutions of financial enslavement of developing countries, they become centers of accumulation of financial resources ensuring the sustainable development of the regional economy, addressing and re- specting the national interests of the participating countries. They provide resourc- es for the social development of the region and form positions for the protection of the national states in international organizations.